IMPROVING INVENTORY ACCOUNTING IN ACCORDANCE WITH INTERNATIONAL STANDARDS (SCIENCE TIME JOURNAL, 2026)
This study explores the improvement of inventory accounting in accordance with international standards, particularly IAS 2 (Inventories). The research analyzes the current practices of inventory recognition, measurement, valuation, and disclosure within national accounting systems and compares them with the requirements of International Financial Reporting Standards (IFRS). Specialattention is given to issues such as cost determination methods, net realizable value assessment, impairment recognition, and financial statement presentation. The paper identifies existing methodological gaps and practical challenges in aligning local accounting regulations with IAS 2. Based on the analysis, recommendations are proposed to enhance transparency, ensure consistency in inventory valuation, and improve the overall quality and reliability of financial reporting in line with internationalstandards.